Development of PBL-Based LKPD to Enhance Students' Mathematical Literacy Skills) - Ismayawati, Ismayawati; Yuliyanti, Sri; Juliangkary, Eliska (Media Pendidikan Matematika, 2025)
This study aims to develop and evaluate a Problem Based Learning (PBL)-based Student Worksheet (LKPD) on polynomial material for 11th-grade students at SMAN 1 Lingsar. The development of the LKPD follows the modified 4-D model, which includes the Define, Design, and Develop stages, due to time and budget constraints. This research employs a one group pre-test and posttest experimental design, involving 30 11th grade students as subjects. The LKPD was validated by two experts: a content expert (80%) and a media expert (90%), who assessed aspects of content accuracy, instructional relevance, clarity, language, simplicity, visual design, and the integration of PBL components. The practicality of the LKPD was measured through questionnaires given to both teachers and students, with results showing a practicality level of 97% in terms of usability and instructional value. The effectiveness of the LKPD was tested through a mathematical literacy assessment given before and after the learning intervention. Data analysis was performed using a paired sample t-test, which showed a statistically significant improvement (p < 0.05) in students' mathematical literacy scores, particularly in problem formulation and solving indicators. These findings empirically support the use of the PBL model as a framework for designing instructional materials that can enhance mathematical literacy. The use of Canva as a design tool also increased student engagement through appealing and functional visual displays. The results of this study demonstrate that contextual and visually designed instructional materials can be effective pedagogical instruments, especially for abstract mathematics topics like polynomials. This research contributes to mathematics education by presenting a validated PBL based LKPD design model that can be adapted for various subjects and educational levels.